2014
DOI: 10.1002/ajoc.201402008
|View full text |Cite
|
Sign up to set email alerts
|

Tripodal Fluorescent Sensor for Encapsulation‐Based Detection of Picric Acid in Water

Abstract: The combination of steric gearing in substituted triethylbenzene and linear structures of 1‐(4‐biphenyl)(benz)imidazolium moieties have been used to design and synthesize tripodal chemosensors with preorganized cavities for detection of picric acid (PA) in (4‐(2‐hydroxyethyl)‐1‐piperazineethanesulfonic acid (HEPES) buffer. The two chemosensors undergo highly selective fluorescence quenching with PA and lead an approximate tenfold increase in KSV values (3.57×105 M−1 and 2.67×105 M−1) and greater than 2000 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Among the highly explosive poly nitro aromatic compounds picric acid is the most devastating one. Although there are reports of selective detection of picric acid616263646566, most of them are not sensitive enough to detect very low level (ppb level) of picric acid. Here we have reported the selective detection of picric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Among the highly explosive poly nitro aromatic compounds picric acid is the most devastating one. Although there are reports of selective detection of picric acid616263646566, most of them are not sensitive enough to detect very low level (ppb level) of picric acid. Here we have reported the selective detection of picric acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the acidic medium, P exists in a protonated form; however, it exists in a neutral form in the basic medium (pH ≤ 10) and could exist in the neutral form. The experimental results indicate that interactions between [ P ] + /[ P ] and picrate anions could be due to columbic interactions (accompanied by a sequential protonation‐aided electron‐transfer mechanism) and synergistic noncovalent interactions, such as intermolecular multiple hydrogen bonding interactions and electron‐rich (anthracene) and electron‐deficient (TNP) ring π–π interactions through a stable charge‐transfer complex, which quenches the anthracene monomer centered at 427 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR and DFT studies of 106 and 107 with PA and X-ray crystal structure of complex of 106 with PA showed the formation of 1:2 stoichiometric complex probe∩2PA formed by replacement of two bromide ions with picrate anions. Tripodal probes 108 and 109 108 (chart 13) as evident from their X-ray crystal structure and DFT optimization studies show that three biphenyl substituents orient on the same side of the triethylbenzene to form a pseudo-cavity which is more preorganised for encapsulation of PA in comparison to that in 106 and 107. Upon excitation at 290 nm, the solution of 108 displayed decrease in emission intensity at 402 nm due to combination of electrostatic, hydrogen-bonding and π-π interactions by picrate anion (Figure 36).…”
Section: Tripodal Tricationic Fluorescent Probes For Picric Acidmentioning
confidence: 99%
“…Further, the detection of vapor of picric acid by fluorescent probe can give advantage for the device formation. However, only in a couple of cases, thin films 108,109,111,120 of probe undergo fluorescence quenching with picric acid within couple of minutes and in other cases the probe deposited on TLC plate 53,89 or the solution of probe in THF-water 33 detect picric acid vapor.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%